Propriedades terapêuticas da díade luminescente de Ru(II): aplicações na inibição e monitoramento da agregação de proteínas amiloides e terapia fotodinâmica antibacteriana - Pereira, Lorena Maria Borges (Universidade Federal de São Carlos, 2025)
Ru(II) metal complexes have attracted considerable attention for biological applications due to their photophysical and photochemical properties. These compounds stand out as luminescent probes and inhibitors of amyloid protein aggregation, as well as potential candidates for use as photosensitizers in antibacterial photodynamic therapy. The aim of this study was to investigate the properties of the Ru(phen)-naphthalenediimide dyad, [Ru(phen)2(pNDIp)]2+, in the aggregation mechanism of human islet amyloid polypeptide (hIAPP) and as a photosensitizer in antibacterial photodynamic therapy. In DMSO solution, the dyad is characterized by an intense absorption band in the ultraviolet region (λMÁX = 265 nm; ε = 83000 M-1.cm-1), typical of intraligand charge transfer (ILCT) transitions of unsaturated aromatic ligands, a structured band in the UV-visible region (300–400 nm) attributed to the naphthalenediimide aromatic core, and a broad absorption band in the visible region (λMÁX = = 450 nm; ε = 15300 M-1.cm-1), assigned to metal-to-ligand charge transfer transitions (MLCT, Ru,dπ → phen,π*), with an emission maximum at 610 nm (λMÁX = 450 nm).Transient absorption studies demonstrated that excitation of the {Ru(phen)3}2+ component of the [Ru(phen)2(pNDIp)]2+ dyad results in rapid electron transfer, generating an intermediate charge-separated excited state (CSS) {Ru3+(phen)2(pNDIp•⁻)}. The assignment of this species as the charge-separated state was confirmed by comparison with spectral features obtained via UV-vis spectroelectrochemistry using the first reduction potential of the {pNDIp} component of the dyad [Ru(phen)2(pNDIp)]2+, and by photolysis with 350 nm light. The dyad demonstrated the ability to monitor hIAPP aggregation kinetics via luminescence, exhibiting behavior similar to the ThT probe. Inhibition assays further revealed that the RupNDIp dyad inhibits the aggregation process of hIAPP in a concentration-dependent manner. Moreover, viability assays conducted in MIN-6 cell lines indicated that the dyad exhibits low cytotoxicity at concentrations ≤100 μM and, when applied in appropriate ratios relative to hIAPP concentration (10 µM), can reduce cytotoxic effects mediated by the fibrillar form of hIAPP. Photodynamic therapy assays against the Gram-negative bacterium Escherichia coli (E. coli) demonstrated the efficacy of the dyad (25 µM). Upon activation with blue light (450 nm), a 4.99 log10 reduction in bacterial viability was observed. These results are associated with additional key features of the compound, including its ability to generate singlet oxygen (1O2) while maintaining photochemical stability. Therefore, the results obtained in this work highlight the potential of the RupNDIp dyad as a versatile compound, exhibiting structural and spectroscopic properties favorable for biological applications.
Therapeutic properties of the luminescent Ru(II) dyad: applications in the inhibition and monitoring of amyloid protein aggregation and antibacterial photodynamic therapy
Keywords: Díade RupNDIp; Amilina ou polipeptídeo amiloide das ilhotas pancreáticas (hIAPP); Sonda luminescente; Terapia fotodinâmica antibacteriana; Fotossensibilizador; RupNDIp dyad; Amylin or human islet amyloid polypeptide (hIAPP); Luminescent probe; Antibacterial photodynamic therapy; Photosensitizer; CIENCIAS EXATAS E DA TERRA::QUIMICA